Fuzzy multi-attribute selection among transportation companies using axiomatic design and analytic hierarchy process - Kulak, Osman; Kahraman, Cengiz (Elsevier BV, 2005)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Axiomatic design; Fuzzy sets; Transportation, logistics and supply chain management; AHP; Information; Transportation company selection; Theory of fuzzy sets, etc.